2004
DOI: 10.1124/jpet.103.059444
|View full text |Cite
|
Sign up to set email alerts
|

Specific Endothelin ETA Receptor Antagonism Does Not Modulate Insulin-Induced Hemodynamic Effects in the Human Kidney, Eye, or Forearm

Abstract: There is evidence that hyperinsulinemia may stimulate endothelin-1 (ET-1) generation or release, which may affect diabetic vascular complications. BQ-123, a specific ET A receptor antagonist, was used to investigate if insulin-induced vascular effects are influenced by an acute ET-1 release. Two randomized, placebo-controlled, double-blind, cross-over studies were performed. In protocol 1, 12 healthy subjects received, on separate study days, infusions of BQ-123 (60 g/min for 30 min) during placebo clamp condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…; Rab et al. ), our study is the first to demonstrate similar effects in LHCs. This paradoxical similarity in FID and ET‐1 response to insulin between LHCs and T2DM subjects suggests either absence of vascular insulin resistance in T2DM or transient development of vascular insulin resistance in LHCs under conditions of acute hyperinsulinemia.…”
Section: Discussionsupporting
confidence: 75%
“…; Rab et al. ), our study is the first to demonstrate similar effects in LHCs. This paradoxical similarity in FID and ET‐1 response to insulin between LHCs and T2DM subjects suggests either absence of vascular insulin resistance in T2DM or transient development of vascular insulin resistance in LHCs under conditions of acute hyperinsulinemia.…”
Section: Discussionsupporting
confidence: 75%
“…These studies unequivocally demonstrate augmented insulin-mediated vasodilation following application of BQ-123, which was not different between groups. An effect of endothelin to limit insulin-stimulated vasodilation has been reported in both animals models (10,22,32,44,45,52) and in insulin-resistant humans (2,25,42). The careful matching of insulin's actions on NO between insulin-sensitive and insulin-resistant subjects before the application of the endothelin antagonist is unique to our study.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, ET-1-induced reductions in insulin sensitivity, and splanchnic and skeletal muscle blood flow were prevented by ET(A) antagonism [70]. In healthy subjects, ET(A) antagonists fail to augment the vasodilation induced by systemic hyperinsulinemia in skeletal muscle vascular beds [153]. Others have reported that ET(A) antagonism revealed insulin-mediated vasodilation which was not evident at baseline [154].…”
Section: Vascular Origins Of Impaired Insulin Actionmentioning
confidence: 90%